ASPEK HUKUM PEMBERIAN TAX AMNESTY SEBAGAI UPAYA UNTUK MENINGKATKAN PENERIMAAN NEGARA DARI SEKTOR PAJAK - Zainal Muttaqin (Indonesian Journal of Dialectics, 2011)
Tax Amnesty is an instrument to increase the income from tax. This instrument however is controversial. There are pros and cons on the part of the Directorate General of Taxation with regard to the loss that the State suffer which will lead to the moral hazard to the Society. Againt this backdround, the Government is in position to draft the Law on Tax Amnesty. In the past however the government had once laid down such provisions as foreseen in the Presidential Decision No. 26 of 1984 in which abolished the administrative sunction and the abolition of tax debt of the previous year and compensated by 1% and 10% of the property subject to tax. The abolition of  sanction and tax amount to the inapplicability of the legal norms and whilst they were undertaken to increase the state income.This research on the tax amnesty is conducted by applying the normative-juridical approach. This approach is appropriate as it to a greater axtent relates to the application of legal norms to the object of the research. The analysis is made qualitatively by applying the legal principles and principles of legislation as well as the legal doctrines.The result of the research show that by referring to the principle of legality, the tax amnesty must be supported and made by the law. In the perspective of justice, however, tax amnesty is not solely based on the so-called “ horizontal and verctical juastices” recognized in the law, but also must be equipped with the transitional justice which will take into account the benefits to be gained. Such gain is to increase the state income while applying the close supervisory mechanism and abiding  law enfocement.